Employment duration and shifts into retirement in the EU - Ted Aranki; Corrado Macchiarelli (European Central Bank (ECB), 2013)
The decision to cease working is traditionally influenced by a wide set of socio-economic and environmental variables. In this paper, we study transitions out of work for 26 EU countries over the period 2004-2009 in order to investigate the determinants of retirement based on the Eurostat Survey on Income and Living Conditions (EU-SILC). Applying standard survivor analysis tools to describe exits into retirement, we do not find any significant differences in the patterns into retirement between the average euro area and EU non-euro area countries. Moreover, we find that shifts into retirement have increased during the onset of the 2009 economic and financial crisis. Income, together with flexible working arrangements, is found to be important as regards early retirement decisions, compared to retiring beyond the legal retirement age. Finally, we show that institutional measures (such as, state/health benefits, minimum retirement age) could not be sufficient alone if individuals withdraw earlier from the labour market due to a weakening of their health. Especially, these latter results are of importance for structural and macroeconomic policy, for instance, in increasing the employment of both people and hours worked against the background of population ageing.
Keywords: J14; J26; C41; 330; ageing population; Cox regressions; duration analysis; EU countries; hazard model; Retirement